A work study on Mirabai Shoppe - Frayna, Ma. Belinda; San Pablo, Maria Lourdes; Santos, Clarisse N. (Diliman, Quezon City College of Engineering, 1996)
The group conducted a work study at the Mirabai Shoppe, a manufacturing firm which produces bags. The study concentrated on the following points : (1) the step by step processes in making KS-45 bag, (2) the plant facilities, equipment, and layout, (3) the manpower, (4) the handling of materials, (5) the setting of standard time, and (6) the office systems and procedures. During the study, the group has seen many areas of the plant's layout and operation which can still be improved on. Problems in housekeeping, ventilation, and plant facilities were observed. The work area was generally cluttered with unnecessary furniture (e.g. china cabinets, piano), equipment and waste materials, and is very hot. Thus, the group proposed on having general cleanings every so often, have little rearrangement of tables and machines, and to have additional units of fans installed. Suggestions to improve workers' facilities were also considered by making sanitary facilities such as soap, toilet paper, hand towels, etc. available. On the other hand, a standard time was established by observing a qualified worker and gathering ten (10) sample times for each element of the operation. Upon conducting studies on the office systems and procedures, considerations were particularly made on the overlapping of job, work overloading, office layout, and on the analysis of forms. The group was able to come up with proposals regarding these problem areas such as (1) having a manual clearly defining each worker's job, (2) doing proper work distribution, (3) making little rearrangement of the office tables and cabinets, and (4) redesigning of forms.
Feasibility study
Keywords: Mirabai Shoppe; Baggage industry; Systems analysis